Designing Aceh Local History Teaching Materials to Strengthen Social Cohesion: A Qualitative Study - Madhan Anis; Aulia Rahman; Okhaifi Prasetyo; Makhroji; Ikhsan Rosyid MA; Teuku Junaidi (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to explore the design process of Acehnese local history teaching materials oriented toward strengthening students’ social cohesion. The research employed a qualitative case study approach involving six social studies teachers, twelve students, and two curriculum developers selected through purposive sampling. Data were collected through classroom observations, interviews with teachers and students, and analysis of curriculum documents and teaching materials. Data were analyzed using Miles and Huberman’s interactive model, which includes data condensation, data display, and conclusion drawing and verification. The findings indicate that local history learning in Aceh remains dominated by elite-centered narratives and does not adequately represent the roles of cross-ethnic and cross-class actors in shaping social cohesion. Empirical evidence shows that integrating alternative sources—such as local archives, oral histories, and multi-perspective case studies—broadens students’ understanding of social cohesion as a historically constructed process formed through interaction and social negotiation rather than as a given condition. These findings underscore that strengthening social cohesion through history education requires a shift from single narratives toward contextual and inclusive instructional design. However, challenges remain in the availability of contextual teaching resources and pedagogical strategies. Overall, the study highlights the importance of systematically designing local history teaching materials aligned with social cohesion theory to enhance the role of history education in fostering national character.